2021
DOI: 10.1063/5.0040947
|View full text |Cite
|
Sign up to set email alerts
|

A direct proof for Maxwell–Wagner effect of heterogeneous interface

Abstract: In this paper, the Maxwell–Wagner effect and the charge characteristics of the heterogeneous interface at the action of higher electric field and elevated temperature are investigated by means of electret technology. A composite membrane with a double-layer structure of a polypropylene (PP) film and a fluorinated ethylene propylene copolymer (FEP) film was made. After being polarized under electric field and elevated temperature, the component PP and FEP films of the composite membranes were separated. The cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
2
16
0
1
Order By: Relevance
“…The great improvement for the d33italiceff value can be attributed to the PDMS–PTFE interface which may itself be an ideal trap for charge retention due to the Maxwell–Wagner phenomenon. [ 49,58–61 ] Thus, the existence of PTFE particles dramatically improves the capability of charge retention. In addition, the process of directly mixing PDMS with PTFE particles is more convenient than the traditional PTFE film coating method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The great improvement for the d33italiceff value can be attributed to the PDMS–PTFE interface which may itself be an ideal trap for charge retention due to the Maxwell–Wagner phenomenon. [ 49,58–61 ] Thus, the existence of PTFE particles dramatically improves the capability of charge retention. In addition, the process of directly mixing PDMS with PTFE particles is more convenient than the traditional PTFE film coating method.…”
Section: Resultsmentioning
confidence: 99%
“…The great improvement for the d eff 33 value can be attributed to the PDMS-PTFE interface which may itself be an ideal trap for charge retention due to the Maxwell-Wagner phenomenon. [49,[58][59][60][61] Thus, the existence of PTFE particles dramatically improves the capability of charge retention.…”
Section: Influence Of Porosity and Filler Weight Ratiomentioning
confidence: 99%
“…The MWS polarization model is useful for studying space charge behavior at the interface in heterogeneous materials. [16,40,41,124] The advantage of this model is to use macroscopic parameters (such as the dielectric constant and conductivity of the material) to discuss the interface charge, without using assumed values of trap depth and activation energy related to carrier injection and transport processes. [32,41,125,126] However, it should be noted that the MWS polarization model suggests that there should be no charge at the interface between the same materials, which contradicts experimental results.…”
Section: Effect Of Interfacial Polarizationmentioning
confidence: 99%
“…The arrangement of Figure 1 shows an electric field applied to an insulating material (polymers for this study) which exhibits one relaxation time shown in Figure 3, a Maxwell-Wagner polarization (Kumara et al, 2020;Li, Chen, et al, 2021;Xu et al, 2017). The shown parallel capacitance 0 t C  is the high-frequency polarization capacitance, which is strange, independent of the frequency bands.…”
Section: Series and Parallel Dielectric Network Of An Insulating Mate...mentioning
confidence: 99%